Stefanova naloga - Južnič, Stanislav (Obzornik za matematiko in fiziko, 2021)
Stefan climbed the Parnassus of the World Science with the support of the mentor, the Bohinj native Marian Koller. The development of research on Stefan Problem is described.
Keywords: Stefanov problem; Stefanova naloga; zgodovina fizike